Description of Pseudopestalotiopsis kubahensis sp. nov., a new species of microfungi from Kubah National Park, Sarawak, Malaysia - Lateef, A.A.; Sepiah, M.; Bolhassan, M.H. (CreamJournal, 2015)
A survey on the diversity and distribution of microfungi was carried out, during which a distinct Pestalotiopsis-like taxa was isolated from green leaves of Macaranga sp. from Kubah National Park, Sarawak. The phylogenetic analysis of DNA sequences from the internal transcribed spacer gene region (ITS1, 5.8S and ITS2) of the rDNA shows this species to form a distinct clade from the Pestalotiopsis, and cluster with the genus Pseudopestalotiopsis, a new genus which was recently carved out from the Pestalotiopsis. This species differs from closely related Pseudopestalotiopsis species such as Ps. cocos, Ps. indica and Ps. theae by its conidial characters such as its unknobbed apical appendages and shorter basal appendages. The new microfungal species, Ps. kubahensis is hereby described based on morphological and molecular data as the fifth species in the genus Pseudopestalotiopsis.